The study of relationship between painful diabetic peripheral neuropathy and functional status of older people in Kuantan - Makhtar, Aniawanis; Syed Elias, Sharifah Munirah; Aziz, Athirah (2019)
Objective: The purpose of this study was to determine the relationship between painful diabetic peripheral neuropathy (PDPN) and functional status among older people in Kuantan, Pahang. Method: A cross sectional design was employed in this study. A total of 300 respondents were selected by convenience sampling method from Endocrine Clinics HTAA and selected clinics in Kuantan. The Short Form McGill Pain Questionnaire 2 (SFMPQ2) was used to characterized and determine the severity of PDPN and Katz ADL Index was used to determine the activities of patient’s daily living. Data was analysed by using SPSS 20.0 version and Descriptive analysis such as mean, standard deviation (SD) and frequency were utilized to describe the characteristics of the respondents. The mean age of the respondents was 68 years old. Result: Spearmen Correlation was utilized to determine the relationship between painful diabetic peripheral neuropathy and functional status. Kruskal Wallis test and Mann Whitney test was conducted in finding the relationship between painful diabetic peripheral neuropathy and socio demographic and clinical characteristic. Conclusion: The result indicates that functional status not significantly associated with the pain. However, race, duration of diabetes mellitus and types of treatment were significantly contributed to pain.